2020
DOI: 10.1007/978-3-030-43851-7_5
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Amine Lewis Base Catalysis in Combination with Transition Metal Catalysis

Abstract: The cooperation between two orthogonal catalytic events during the formation of carbon-carbon and carbon-heteroatom bonds has emerged as an effective strategy for enantioselective chemical synthesis. In recent years, a number of pioneering investigations have described useful chemical synthesis methods whereby the reactivity or nucleophile-electrophile combinations can be fine-tuned or extended far beyond the effect and influence of a single catalyst. The recognition of this has had profound implications for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In 2013, Carreira and co-workers reported pioneering work involving dual iridium and amine catalysts for stereodivergent α-allylic alkylation of aldehydes (Figure A). Since then, synergistic catalysis has emerged as a powerful and commonly used strategy for achieving stereodivergent synthesis (Figure B). The Zhang and Wang research groups have independently reported on an iridium/copper bimetallic system that enables stereodivergent allylation of aldimine esters. The Hartwig group has employed a synergistic iridium/copper catalysis method for stereodivergent allylation of azaaryl acetamides.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Carreira and co-workers reported pioneering work involving dual iridium and amine catalysts for stereodivergent α-allylic alkylation of aldehydes (Figure A). Since then, synergistic catalysis has emerged as a powerful and commonly used strategy for achieving stereodivergent synthesis (Figure B). The Zhang and Wang research groups have independently reported on an iridium/copper bimetallic system that enables stereodivergent allylation of aldimine esters. The Hartwig group has employed a synergistic iridium/copper catalysis method for stereodivergent allylation of azaaryl acetamides.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Snaddon has reviewed the general combination of chiral tertiary amine Lewis base catalysis with chiral transition metal catalysis. 14 This review will inspect developments since 2016 in the deployment of a chiral aminocatalyst with an achiral metal catalyst. Specifically, the reactions we will analyse here are examples of ‘Type I’ systems in which each catalyst acts independently and fully cooperatively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, to address these issues, a synergistic strategy has been adopted where a second chiral catalyst is used to activate the pronucleophiles and provide stereocontrol during the bond-forming events (Figure b). In 2016, Snaddon and co-workers reported the use of a chiral Lewis base and an achiral Pd-complex in the direct α-allylation of perfluorophenyl arylacetic esters, wherein the stereocontrol was provided by the nucleophilic chiral Lewis base catalyst rather than the Pd-based ligand frameworks . In 2018, Shimizu, Kanai, and co-workers developed a boron/palladium dual catalysis for an asymmetric migratory α-allylation of allyl esters, resulting in α-allyl carboxylic acids containing an α-quaternary stereocenter .…”
mentioning
confidence: 99%